Implementation of Line of Sight Algorithm Design Using Quadcopter on Square Tracking - Anggara Trisna Nugraha; Dimas Rinaldi; Muhammad Syahid Messiah; Muhammad Jafar Shiddiq; Moch Fadhil Ramadhan; Fortunaviaza Habib Ainudin (Universitas Negeri Malang, 2022)
The improvement of the quadcopter has extended its function, even for risky army tasks, i.e., search, reconnaissance, and rescue operations. The quadcopter also can be implemented for medical tasks, such as mapping wind velocity conditions, detecting radiation sources, surveillance, and upkeep and surveys. A quadcopter is a non-linear machine with more than one enter and output and a machine with balance problems. It is simply prone to outside disturbance. This function reasons a few problems in controlling the monitoring motion and adjusting the dealing with the path automatically. Based on those problems, this looks like the monitoring manipulated layout within the horizontal place with the aid of including the line of sight's set of rules. So, that direction following converges closer to 0 and may conquer the disturbance of ocean currents that extrude the parameters of the quadcopter in shifting at the horizontal place. The controller benefit is acquired using the numerical iterative of the Linear Matrix Inequality (LMI) technique. Meanwhile, Command-Generator Tracker (CGT) controls the monitoring function at the x and y. The simulation effects display that the manipulation technique can deliver the yaw, pitch, and roll to the anticipated values on a rectangular track.DOI: 10.17977/um024v7i22022p099